Parental knowledge levels regarding the care and nurturing of preterm infants - Malgorzata Barbara Wójtowicz-Szefler; Hanna Bachurska (Medical Research Journal)
INTRODUCTION: Parental knowledge about care, nurturing, and feeding plays a crucial role in minimizing complications and supporting healthy development. However, research indicates that parents often lack sufficient knowledge in key areas, contributing to increased stress, anxiety, and inadequate care for preterm infants. OBJECTIVE: The primary aim of the study was to assess parents’ knowledge levels concerning the feeding, care, and nurturing of preterm infants. Additionally, the study sought to determine whether sociodemographic variables influenced the parents’ knowledge levels. MATERIALS AND METHODS: The study applied a proprietary questionnaire, which consisted of 42 questions. A total of 115 parents participated, including 63 mothers and 52 fathers. The assessment of parental knowledge was conducted using the custom-developed 42-item questionnaire (Wójtowicz-Szefler, Bachurska). RESULTS: Among the 115 participants, 36.52% demonstrated a moderate and low level of overall knowledge, 20.84% a good level. Only 6.09% achieved a high level of knowledge. A strong correlation was found between knowledge of feeding and care (R = 0.733, R2 = 0.53, p < 0,05) as well as between feeding and nurturing (R = 0.785, R2 = 0.61, p < 0.05). Sex, age, and education significantly influenced knowledge levels; women and individuals aged 26–35 years with higher education achieved better results. CONCLUSIONS: The study reveals insufficient parental knowledge regarding the care, nurturing, and feeding of preterm infants, with only a small percentage demonstrating a high level of competence. Strong correlations between feeding and both care and nurturing suggest the need for integrated educational approaches.